Effect of different growing substrates on growth characteristics of Plectranthus sp. in the interior green wall - Mohammad Ali Golestani; Mahmoud Shoor; Ali Tehranifar; Mohammad Hossein Neamati (علوم محیطی)
Introduction: One of the most important issues in the implementation of interior green walls is choosing an efficient and light medium. In recent years, the use of soilless culture in the world, including Iran, has been developing. In this regard, the use of agricultural organic waste in culture media can play an important role in achieving a sustainable environment in addition to its economic advantages. Therefore, this study aimed to compare the effect of imported media and agricultural organic waste on growth characteristics of Plectranthus plant. Material and methods: In this study, the effect of five different growing substrates on the growth characteristics of Plectranthus was performed in a randomized complete block design with four replications and volume ratios (60 to 40) of 1) peat moss + perlite; 2) compost mixes used by greenhouse growers (rice husk compost + tea waste + leaf soil+ rice hull) + perlite, 3) leaf soil compost + perlite, 4) rice hull compost + perlite, and 5) tea waste compost + perlite. In this study, growth traits such as the number of leaves and shoots, fresh and dry weights of shoots and roots, physical properties of media, such as bulk and particle density, water holding capacity, and chemical properties including organic matter percentage, pH, electrical conductivity of the substrate, percentage of phosphorus, nitrogen, potassium, organic carbon, cation exchange capacity, and C/N ratio were measured. Results and discussion: The physicochemical analysis of the combined substrates showed that the composition of the tea waste and perlite had superiority over other media in terms of nitrogen content, water holding capacity, organic matter, and organic carbon percentage, as well as cation exchange capacity. In addition, the lower bulk density in the waste tea and perlite medium (0.15 g/cm-3 ) can be an ideal indicator of its application in the interior green walls compared to the other studied media. Results of the analysis of variance showed that different growing substrates had a significant effect (P ≤ 0.01) on the growth characteristics of the Plectranthus ornamental plant. So that, Plectranthus plants grown on tea waste compost + perlite showed superiority in all measured traits in comparison with other media. One of the important indicators for evaluating substrates is the dry weight of the shoots. In this study, plants grown on tea waste compost + perlite media had higher shoot dry weight and leaf number, which could be due to higher cation exchange capacity and nitrogen content in these media. In contrast, the plants grown in the media of rice husk compost + perlite had the lowest growth characteristic compared to other treatments. The decrease in growth parameters in this substrate can be attributed to the low percentage of nutrients, water holding capacity, and cation exchange capacity. Conclusion: According to the results of this study, the combined substrate of tea waste compost+ perlite, can be a good substitute for imported peat moss in the interior green walls and sustainable green space development due to its proper nutritional characteristics, and low substrate weight and cost, as well as the abundance of these substrates in factories of northern Iran.